The effect of diabetes mellitus on outcomes of patients with nosocomial pneumonia caused by methicillin-resistant Staphylococcus aureus: data from a prospective double-blind clinical trial comparing treatment with linezolid versus vancomycin. Issue 1 (December 2016) - Equils, Ozlem; da Costa, Christopher; Wible, Michele; Lipsky, Benjamin
Abstract Background The presence of diabetes mellitus increases the risk of several severe infections, but data on its effect on treatment outcomes in patients with nosocomial pneumonia (NP) caused by methicillin-resistantStaphylococcus aureus (MRSA) are limited. Methods We retrospectively analyzed data from a double-blind, randomized, multi-center, international clinical trial of culture-confirmed MRSA NP that compared treatment with linezolid to vancomycin. Specifically, we evaluated the clinical and microbiologic outcomes of patients with and without diabetes in the modified intent to treat population at end-of-treatment (EOT) and end-of-study (EOS, 7–30 days post-EOT). Results Among 448 enrolled patients 183 (40.8 %) had diabetes mellitus, 87 (47.5 %) of whom received linezolid and 96 (52.5 %) vancomycin. Baseline demographic and clinical characteristics were similar for the two treatment groups. Clinical success rates at EOS were 57.6 % with linezolid and 39.3 % with vancomycin, while microbiological success rates were 58.9 % with linezolid and 41.1 % with vancomycin. Among diabetic patients, rates of mortality and study drug-related adverse effects were similar between the treatment groups. Overall day 28 mortality rates were higher among diabetic patients compared to non-diabetic patients (23.5 vs 14.7 %, respectively: RD = 8.8 %, 95 % CI [1.4, 16.3]). Conclusions Among diabetic patients with MRSA NP, treatment with linezolid, compared to vancomycin, was associated with higher clinical and microbiologic success rates, and comparable adverse event rates. Trial registration NCT00084266 .